Forestry Education in India: The Lasting Value - Sagar, Naincy; Subba, Susmita (International Journal of Economic Plants, 2021)
The protection and management of forest resources have always been engulfed in the Indian heritage since ages along with the contribution of the ecosystem and its services. India is not only famous for its diverse wildlife and culture, but also for its dense and vast forest cover. Indian climate befits the variety of flora and fauna. B.Sc. Forestry course provides an insight to subjects regarding silviculture, tree improvement, forest products, mensuration, forest management and others and the student are also provided with professional training in some universities in India like weapon training, etc. The course B.Sc. forestry which provides knowledge to this science is still not as popular in the country as the subject agriculture is recognized. The inadequacy in jobs and opportunities for the thousand of forestry graduates has lessened the wide scope of this course. The recent awareness of the world in the protection and effective management of forest resources has increased massively the importance of courses like B.Sc. forestry in national as well as international organizations. This is the ‘golden hour’ for a course like forestry in government and private sectors from centre, state to research perspectives. However, a little reform in some structure of the recruitment policies of the graduates could massively create employment for the foresters.